Distribution of genetic markers at workers of aluminum industry with professional fluorosis: serum proteins and erythrocyte isoenzymes - N. I. Gafarov (Acta Biomedica Scientifica)
The aim of this work was the study of the association of biochemical markers of genes with the risk of the development of professional and work-related fluorosis in people, working in the aluminum industry. From 303 to 387 employees of Novokuznetsk aluminum factory were examined for various polymorphic genetic systems. The main group consisted of patients with fluorosis who were tested in the clinic of Research Institute of Complex Problems of Hygiene and Occupational Diseases RAMS. The control group (110 people) consisted of apparently healthy individuals of the same professions, working on Novokuznetsk aluminum factory, but without a diagnosis of occupational disease. We studied the serum proteins haptoglobin (HP), group-specific component GC, erythrocyte acid phosphatase ACP, fluorescent esterase EsD, protease inhibitor a-1-antitrypsin AAT. The material for the study was the venous blood samples. The study was conducted with the use of electrophoresis in polyacrylamide and the starch gels followed by histochemical staining electrophoregrams. Variants of protease inhibitor a-1-antitrypsin (AAT) were separated by isoelectric focusing in polyacrylamide gel. For analyzing the association studies of gene markers of the risk of develop ment (or resistance to the development) of fluorosis the criteria χ2 and OR were used. It was revealed that variants AcP aa, AcP bb, AcP bc, EsD 2-2, PI M3M3 and GC, combinations (1-1) + PI (MR), GC (11) + PI (M3M3), PI ( MR) + EsD (2-2), GC (1-1) + PI (M2M3), EsD (2-2) + AcP aa, GC (1-1) + EsD (2-2) referred to the risk genotypes of development of fluorosis. Two-component combinations of genotypes that were also associated with an increased risk of development of professional fluorosis were identified: GC (1-1) + PI (MR), GC (1-1) + PI (M3M3), PI (MR) + EsD (2-2 ); GC (1-1) + PI (M2M3), EsD (2-2) + AcP aa; GC (1-1) + EsD (2-2). For three-way combinations of genotypes are GC (1-1) + PI (MR) + AcP AA and GC (1-1) + EsD (2-2) + AcP cc. Genotypes resistant variants are: PI M1M1, EsD 1-1, AcP ab, AcP ac.